Influence Of Technology Professional- Development on Teachers Self-Efficacy in The Use of ICT For Teaching Basic Science and Technology - Joy Peter; Ahmed Idris ISSA; Kate Uzoamaka Bonse (International Journal of Advanced Humanities Research)
The aim of this study was to assess the impact of technology professional development on teachers' self-efficacy in using Information Communication Technologies (ICT) for teaching in Abuja Metropolis. This study (i) assessed the technology professional development teachers have access to; (ii) determined the level of teachers’ technology professional development; and (iii) determined the level of teachers’ self-efficacy in the use of ICT for teaching; Methods: This research adopted descriptive research of the survey type. Participate: 338 teachers were randomly selected. The research instrument used for data collection is a questionnaire. Research questions 1, 2 and 3 were answered using mean score and percentages while the formulated hypothesis was tested using the t-test at 5% margin of error and at 95% confidence level. The result: the technology professional development that teachers have access to in Abuja metropolis are conferences, seminars and workshops.level of teacher’s technology professional development in Abuja metropolis is high. the level of teacher’s self-efficacy in the use of ICT for teaching in Abuja metropolis is average and teachers’ gender does not influence the technology professional development. The study recommended that among others that funds, ICT facilities, and trained teachers should be provided for the effective use of technology professional development on teachers’ self-efficacy in the use of ICT for teaching in Abuja Metropolis.